Isospin effect of the in-medium nucleon-nucleon cross section in excited nuclear reactions - 张傲 郭文军 黄江伟 杨林孟 (Chinese physics C, 2014)
Using relativistic mean field theory, the neutron and the proton density distribution of 56Ni nuclei could be obtained in the ground state and the excited state. Based on the framework of the quantum molecular dynamics model, the 56Ni nuclei have been simulated in ground state and in the neutron or proton excited state. We then used the three different states of 56Ni to collide with the 56Ni in the ground state. To discuss the evolution of the nuclear stopping in different reactions, two kinds of different excited nuclear reactions were studied at different reaction energies and at different impact parameters. Studies have shown that the nuclear stopping of an excited nuclear reaction is sensitive to the isospin-dependent in-medium nucleon-nucleon cross section, compared with the response value of the ground state nuclear reaction. So, it is better for the excited nuclei to extract the isospin dependence of nucleon-nucleon cross section information.